Huntington Beach 4th of July Parade with Watkins Family and Model T Ford - Watkins, Howard::::::::: (1988)
Jerry Kamp, Carol, Frances Kamp, Robin Watkins, Adam Watkins, Albert Watkins, and Howard Watkins (driving and wearing Cherokee Indian headdress in Watkins Family Model T Ford